"Nous étions ici pour durer:" Memorialization and Environmental Advocacy in Véronique Tadjo's En compagnie des hommes. Issue 4 (8th August 2021) - Messay, Marda
Abstract: This article focuses on the ecological issues raised in Véronique Tadjo's En compagnie des hommes (2017), a novel on the deadliest outbreak of Ebola in Guinea, Liberia and Sierra Leone from 2014 to 2016. It examines how Tadjo uses non-human narrators (a Baobab, a Bat, and the Ebola virus) to bear witness to an ancestral environmental ethos, to denounce humans' environmentally violent practices, and to underscore the need to challenge and decenter humans' dangerous anthropocentric position. It also studies how Tadjo uses human narrators to document the disruptions caused by the Ebola virus in their relationship with nature, specifically the disruption in burial rites and the role of guérisseurs (traditional healers). In this article, I argue that En compagnie des hommes is not only a memorial to nature and to humans' interrelationship with the natural world, it also advocates for the repair of that relationship and for acting ethically and respectfully toward nature and non-humans.